2015
DOI: 10.3923/ajava.2015.527.536
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Indian Naked Neck Chicken Under Tropical Climatic Conditions

Abstract: The three naked neck broiler genotypes (NaNa, Nana and nana) were investigated for the effect of temperature on juvenile body weights, shank length, immune competence and carcass characteristics. Weekly body weights were recorded from day old to six weeks (n = 417). The body weights were significantly higher in naked neck genotypes (NaNa and Nana) at 4th, 5th and 6th week of age. Birds with NaNa and Nana genotype recorded significantly (p#0.05) higher weight gains during 4th (211.17 g) and 5th (207.96 g) week,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The mortality of birds between 1 -8 weeks of age was 6-9 % whereas the mortality in 8-20 weeks age group was 5.47 % which corroborates the findings of Nandi et al, (2017) and Mohanta, et al, (2018). The shank length is very high in males (1.12 ± 0.22 cm) whereas the females have the normal shank (9.78 ± 0.24 cm) which is in line with Daikwo et al, (2011);Padhi et al, (2015); Reddy et al, (2015) and Das et al, (2016) who reported comparable shank length in females. The egg weight, adult body weight and shank length are better than the registered Hansli bird of Odisha (ICAR-NBAGR, 2018).…”
Section: Quantitative Parameterssupporting
confidence: 84%
See 2 more Smart Citations
“…The mortality of birds between 1 -8 weeks of age was 6-9 % whereas the mortality in 8-20 weeks age group was 5.47 % which corroborates the findings of Nandi et al, (2017) and Mohanta, et al, (2018). The shank length is very high in males (1.12 ± 0.22 cm) whereas the females have the normal shank (9.78 ± 0.24 cm) which is in line with Daikwo et al, (2011);Padhi et al, (2015); Reddy et al, (2015) and Das et al, (2016) who reported comparable shank length in females. The egg weight, adult body weight and shank length are better than the registered Hansli bird of Odisha (ICAR-NBAGR, 2018).…”
Section: Quantitative Parameterssupporting
confidence: 84%
“…Other visible specific traits such as well-developed spur in adult males having fairly long neck with plenty of hackle feathers. The beak is fairly long, pointed at tip and light yellow in colour while wings are large in size well folded (Hailemichael et al, 2015;Hareesh and Guru Vishnu, 2015). The plumage colour of this bird is black breasted red and birchen while the registered breed Hansli is mostly black and solid (Eskindir et al, 2013).…”
Section: Qualitative Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The heavier neck weight associated with the Na gene could be attributed to the feather reduction associated with this gene, consequently saving more protein for muscle weight as reported by other researchers ( Adedeji et al., 2006 , Galal et al., 2007 ). According to Reddy et al., (2015) , reduced feather coverage helps to improve and enhance heat dissipation and consequently alleviate the effects of heat on chickens reared in hot climates. In addition, reduced feathering saves on the amount of protein required to form feathers, and such protein that would have been used to form feather would now be used for meat tissue development.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the majority of relevant reports have shown that naked neck and frizzle genotypes have higher antibody production against SRBC under high ambient temperatures (Kundu et al 1999; https://doi.org/10.17221/221/2018-CJAS Fathi et al 2005Fathi et al , 2014Rajkumar et al 2010). A higher titre against NDV was observed in naked neck genotypes (NaNaff and Nanaff) compared to normal plumage (nanaff) under tropical climatic conditions (Reddy et al 2015).…”
Section: Immune Responsementioning
confidence: 89%